COMPETITIVENESS TOWARDS ASEAN ECONOMIC COMMUNITY - Pangestu, Mari Elka (Journal of Indonesian Economy and Business, 2009)
ASEAN Economic Community will be the driving force of an economic integration within ASEAN countries, and between ASEAN countries and the rest of the world. Many believe the economic integration will realize ASEAN framework as a single market and production base, to increase competitive economic region, to support more equitable economic development, and as a stepping stone toward full integration into globaleconomy. Commitments of the implementation of AEC Blueprint by ASEAN member countries will be a crucial role to achieve the objective of the ASEAN Vision, Mission, and Targets.Keywords: AEC, ASEAN, Economic Community